Reading law : the interpretation of legal texts - Scalia, Antonin; Garner, Bryan A. (Thomson/West, 2012)
In this groundbreaking book, Scalia and Garner systematically explain all the most important principles of constitutional, statutory, and contractual interpretation in an engaging and informative style - with hundreds of illustrations from actual cases. Is a burrito a sandwich? Is a corporation entitled to personal privacy? If you trade a gun for drugs, are you "using a gun" in a drug transaction? The authors grapple with these and dozens of equally curious questions while explaining the most principled, lucid, and reliable techniques for deriving meaning from authoritative texts. Meanwhile, the book takes up some of the most controversial issues in modern jurisprudence. The authors write with a well-argued point of view that is definitive yet nuanced, straightforward yet sophisticated. - Publisher